(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Drought is a major abiotic stress severely limiting rice production, especially in rain-fed ecosystems. The present study evaluated the drought tolerance and yield stability of four advanced rice mutants developed by the Bangladesh Institute of Nuclear Agriculture (BINA), alongside drought-tolerant BRRI dhan56 and susceptible Binadhan-7 checks, across three different drought-prone environments in Bangladesh. A twenty-one-day irrigation withdrawal was imposed post-transplanting to simulate drought stress during the early to maximum tillering stage. Results revealed an average yield reduction of 51.84% for grain and 51.17% for straw under drought. Among the genotypes, mutants M-3 and M-4 showed superior resilience, with minimal reductions in key yield components like filled grains panicle-1, and effective tiller number. Correlation and Principal Component Analysis (PCA) identified filled grains panicle-1 as a critical trait for selection under stress. Stability analyses using phenotypic indices, regression coefficients, and GGE biplot confirmed M-3 and M-4 as high-yielding and stable across environments. GGE biplot also highlighted Rangpur’s high discriminative power for evaluating drought responsiveness. The susceptible check Binadhan-7 showed the poorest performance and the highest environmental sensitivity. These findings demonstrate the genetic potential of M-3 and M-4 as drought-resilient genotypes and as valuable donors in future breeding programs. Bangladesh J. Nuclear Agric, 39(2): 1-16, 2025